PENGARUH KONFLIK PERAN GANDA DAN STRESS KERJA TERHADAP KINERJA DOSEN WANITA DI FAKULTAS EKONOMI UNIVERSITAS JAMBI - Sry Rosita (Manajemen Bisnis, 2012)
Sry RositaUniversitas Negeri JambiE-mail: sryrosita@gmail.comABSTRACTWork and family is two Women’s responsibilities Lecturer in the Faculty of Economics, University ofJambi, or often referred to as a dual role. Conditions such as the above can lead to a dual roleconflict which if left unchecked can lead to job stress in daily life and can lead to poor performancein particular women Lecturer in the Faculty of Economics University of Edinburgh. Stress is a naturalstate for human beings formed as a response to and a part of the everyday life of the first man to facethe era advances all areas faced with the hustle and bustle to be done. There are 4 types of stressorsthat affect job stress, namely: 1. Stresors Outside Organizations 2. Stresors 3 Organization. StressorsIndividual Level 4. Group level stressors. While the performance of a faculty member judged by TriDarma University is to conduct education, research, and Community Services and Allied Duties plusTridharma High. The main objective of this study to obtain empirical evidence about the influence ofDual Role Conflict and Job Stress on Performance Female Lecturer at the Faculty of Economics,University of Edinburgh, using sampling techniques such as random sampling. The data collectionmethod is by using questionnaires. Techniques of data analysis in this study is multiple regressionanalysis.Keywords: Dual Role Conflict, Work Stress, Performance Lecturer